Hubungan pola makan, konsumsi kopi dan Tingkat Stres Dengan Kejadian Gastritis Di Wilayah Kerja BLUD UPTD Puskesmas Poasia Tahun 2024 - Fitriani, Fitriani; Yuniar, Nani; Tungga Dewi, Sri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Gastritis, commonly known as ulcers, is inflammation or bleeding in the lining of the stomach caused by an unhealthy lifestyle. To determine whether there is a relationship between diet, coffee consumption, and stress levels with the incidence of gastritis in the BLUD UPTD Poasia Health Center work area in 2024. This study used a quantitative research method using a cross-sectional design approach. The results showed that diet (p-value = 0.00), coffee consumption (p-value = 0.00), and stress levels (p-value = 0.00). The results showed that there was a relationship between diet, coffee consumption, and stress levels with the incidence of gastritis in the BLUD UPTD Poasia Health Center work area in 2024